The Antibacterial Activity of Locally Grown Turmeric (Guyana) Using Ethanol Extracts at Different Concentrations against Escherichia Coli, Proteus Vulgaris, Pseudomonas Aeruginosa and Staphylococcus Aureus - Persaud, Nirvanie; Ragobeer, Paulette; Daniel, Ruth (The Asia Journal of Applied Microbiology, 2020)
The present study was conducted to investigate the antibacterial activity of ethanol extracts of turmeric (Curcuma longa L.) locally grown in Guyana against the different strains of bacteria, namely Escherichia coli, Proteus vulgaris, Pseudomonas aeruginosa and Staphylococcus aureus. Different concentrations of the turmeric extract were prepared ranging from 100%, 75%, 50% and 25% using the solvent 95% ethanol. The antibacterial activity was tested against the aforementioned bacterial strains at the different concentrations of the extract using the disc diffusion method. According to the results, the ethanolic turmeric extract exhibited considerable antibacterial activity against all the tested bacteria. Maximum antibacterial activity was seen at 25% concentration against three of the tested bacteria, namely E. coli, P. aeruginosa and S. aureus. Overall, the effect of the ethanolic turmeric extract varied with the concentrations against the four tested bacteria whereby Pseudomonas aeruginosa was the most susceptible to the extracts while Proteus vulgaris was the most resistant. The use of ethanolic turmeric extract as an antibacterial agent in treatment of infections caused by bacteria has been suggested by many researchers.